STUDI DESKRIPTIF KUALITAS PRODUK OLI CASTROL POWER 1 4T BERDASARKAN PERPSEPSI KONSUMEN DI SURABAYA - Ignasius Victor (Perpustakaan Universitas Surabaya, 2014)
This study aims to determine the quality of the description of Castrol Power 1 4T oil by consumer perceptions in Surabaya . This study used kuantitatif descriptive purely with software SPSS for windows 18 , this study uses a survey method . Determination of population using non-probability sampling techniques and sampling methods using convenience sampling, data processing method using cross- tabulation with the characteristics of the target population is the consumers who have purchased and use Castrol Power 1 4T oil for 4 months on a regular basis and at least 17 years old with a high school education level. The samples used in this study a total of 120 samples. The results of this study indicate that picture of the quality of oil products Castrol Power 1 4T in Surabaya seen from the 8 dimensions of quality of products; Performance, Feature, Reliability, Conformance, Durability, Serviceability, Aesthetics, Perceived Quality, the quality of the product oil Castrol Power 1 4T in Surabaya quality perceived by consumers .